Professional norms and physician behavior: homo oeconomicus or homo hippocraticus? - Iris Kesternich; Heiner Schumacher; Joachim Winter (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2014)
Physicians' treatment decisions determine the level of health care spending to a large extent. The analysis of physician agency describes how doctors trade off their own and their patients' benefits, with a third party (such as the collective of insured individuals or the taxpayers) bearing the costs. Professional norms are viewed as restraining physicians' self-interest and as introducing altruism towards the patient. We present a controlled experiment that analyzes the impact of professional norms on prospective physicians' trade-offs between her own profits, the patients' benefits, and the payers' expenses for medical care. We find that professional norms derived from the Hippocratic tradition shift weight to the patient in the physician's decisions while decreasing his self-interest and efficiency concerns.
urn:nbn:de:bvb:19-epub-18991-8
Keywords: A13; I19; C72; C91; 330; social preferences; allocation of medical resources; professional norms